Strategic prospective to the textile sector of the district of San Juan Lurigancho - Inche Mitma, Jorge (2009)
This article is about the next problem how to formulate a strategic scenario to textile sector of San Juan de Lurigancho district?, in order to achieved the French Method of the Strategic Prospective was used, being obtained a series of possible prospective scenarios, selecting among them the bets scenario, identifying previously the principals variables and the system actors behavior.